Whether Environmental Performance Can Strengthen Corporate Governance Relationship To Carbon Emission Disclsoure - Ulfa Ulfa; Khomsiyah Khomsiyah (Journal Of Social Science (JoSS), 2023)
This research aims to examine the impact of the correlation between corporate governance and moderated carbon emission disclosure and environmental performance. This study used secondary data using purposive sampling techniques. Twelve companies met the specified criteria and obtained 60 data during the research period from 2017 to 2021. The data analysis technique used is "Moderated Regression Analysis (MRA)." From the results of research on corporate governance, it negatively affects carbon emission disclosure, and environmental performance negatively affects carbon emission disclosure. Environmental performance deduces the correlation between corporate governance and carbon emission disclosure.